2001
DOI: 10.1128/iai.69.12.7772-7782.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analysis of the Yersiniabactin Receptor Gene fyuA and the Heme Receptor hemR of Yersinia enterocolitica In Vitro and In Vivo Using the Reporter Genes for Green Fluorescent Protein and Luciferase

Abstract: The enteropathogenic Yersinia enterocolitica strains have several systems for scavenging iron from their environment. We have studied the expression of the fyuA gene, which encodes the outer membrane receptor for the siderophore yersiniabactin (Ybt), and the hemR gene, which encodes the receptor for heme, using the reporter genes gfp (encoding green fluorescent protein) and luc (encoding firefly luciferase). To study gene expression in vitro as well as in vivo, we have constructed several translational reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
0
26
0
2
Order By: Relevance
“…To determine if yersiniae no longer expressing RFP or GFP were present in microcolonies, we also immunostained cryosections of Y. enterocolitica-infected mouse organs 5 days p.i. with antiYadA rabbit antiserum followed by an anti-rabbit fluorescein isothiocyanate-or tetramethyl rhodamine isocyanate-conjugated antibody as previously described (20). This immunostaining revealed that all yersiniae and microcolonies in the tissue sections were detectable by RFP or GFP fluorescence (data not shown), indicating the reliable expression of the reporter genes and the maintenance of the reporter plasmids during the infection experiments.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…To determine if yersiniae no longer expressing RFP or GFP were present in microcolonies, we also immunostained cryosections of Y. enterocolitica-infected mouse organs 5 days p.i. with antiYadA rabbit antiserum followed by an anti-rabbit fluorescein isothiocyanate-or tetramethyl rhodamine isocyanate-conjugated antibody as previously described (20). This immunostaining revealed that all yersiniae and microcolonies in the tissue sections were detectable by RFP or GFP fluorescence (data not shown), indicating the reliable expression of the reporter genes and the maintenance of the reporter plasmids during the infection experiments.…”
Section: Resultsmentioning
confidence: 96%
“…For the detection of yersiniae by immunofluorescence, cryosections were fixed with 3.7% paraformaldehyde and incubated for 30 min in 2% bovine serum albumin to block nonspecific binding. Bacteria were stained with a primary monoclonal YadA antibody and a fluorescein isothiocyanate-or tetramethyl rhodamine isocyanatelabeled secondary antibody as previously described (20). Composite images of PPs, livers, and spleens were automatically assembled using a motorized Olympus BX61 fluorescence microscope with analysis software (Olympus Soft Imaging System).…”
Section: Methodsmentioning
confidence: 99%
“…The HPI is a long chromosomal fragment containing several regulatory genes and the genes related to synthesis, uptake, and transport of siderophores such as yersiniabactin (Ybt), which is involved in the virulence and pathogenicity of Yersinia species (Rakin et al 1999, Jacobi et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…The functionality of yersiniabactin biosynthesis was evaluated by detecting the presence of yersiniabactin in the cell-free supernatant of iron-starved bacteria by using a translational reporter gene fusion system with luciferase (20,28). Synthesis and release of yersiniabactin were observed in all HPI-positive strains tested except 1380, which carries a truncated island, and 50/90 and HPI-negative control strains (Table 1).…”
mentioning
confidence: 99%